Cultura de segurança do paciente na atenção domiciliar: perspectiva da equipe de saúde e do cuidador - Soppa, Francielli Brito da Fonseca (2018)
Field study on patient’s safety culture in home care (AD), from the caregiver perspective, alongside with Program of home attention and internment (PAID), taking place in the city of Cascavel, Parana. Data collection occurred at three moments: At the first moment 28 staff professionals answered a Safety Attitude Questionnaire (SAQ) and complementary instrument. During the second and third moments, there were semi structured interviews with 10 caregivers and 9 professionals who act alongside with them. Descriptive statistics analyzed quantitative data, while the analysis of qualitative data occurred through a process based on thematic review, dialoging with literature on this subject. Patient’s safety culture in home care (AD) has shown some shortcomings, notably the dimensions which reflect managing actions. The conclusion of SAQ, which contained workers’ suggestions for the improvement of patient’s safety in home care (AD), highlighted the professionals’ good perception, enabling the exposure of various challenges that involve this topic. Such difficulties characterize themselves by the need to implement strategies, such as having an open hospital door in critical situations, elaborating and applying protocols, regular availability of materials and facilities, in addition to emotional support for the patient, their family and the caregiver. Staff emphasized the permanent education in health (EPS) as strategies changing biomedical model in assistance; the need of identifying the mistake and notifying the professional about it among educational and service institutions to take effective actions. Results showed that women still represent 90% of caregivers are women, 90% are family members and 89% of them are the only responsible for such duty, which contributes to their emotional and physical illness. The impacts of being a caregiver as well as the difficulties found in their daily activities are evidences that caregivers’ teaching, learning and doing base themselves on their bond with health care staff, when it comes to patient’s safety practices and the promotion of a safe environment in home care (AD). Thus, providing safe home care is a challenge for macro and micro policies to overcome interventions centered in biomedical model and utilitarian perspective of home care (AD), contributing to strengthen patient’s safety culture to improve a better health assistance.